Mesenchymal Stem Cell Treatment of Disc Lesion Prevents Fatty Infiltration and Fibrosis, but not Muscle Fibre Transformation of the Multifidus Muscle. Issue 1 (April 2016) - Hodges, Paul; James, Greg; Hall, Leanne; Schmid, Annina; Shu, Cindy; Little, Chris; Melrose, James
Introduction: The multifidus muscle undergoes structural and behavioral changes with back pain and injury. After intervertebral disc (IVD) lesion in animals the multifidus muscle undergoes a transformation of muscle fiber types from slow-to-fast, and extensive structural remodelling with increased adipose and connective tissue. Increased expression of pro-inflammatory cytokines (tumor necrosis factor (TNF) and interleukin 1β (ΙΛ−1β)) parallel these changes and may be responsible. Treatment of IVD lesions with mesenchymal stem cells (MSC) prevents or restores loss of IVD height and proteoglycans in the nucleus pulposus, depending on the timing of application. Whether the resolution of IVD changes by MCS treatment prevents or restores changes in the multifidus muscle structure and muscle fiber composition is unknown. This study aimed to investigate whether muscle changes are prevented or restored by early or late MSC treatment of the IVD lesion, respectively, and whether this is related to modification of inflammatory cytokine expression. Material and Methods: The L1–2 and L3–4 IVDs of 18 sheep received left anterolateral partial thickness annular lesions. Six control sheep underwent no surgery. At four (3-month ( n  = 6) and 6-month acute ( n  = 6) treatment groups) or twelve (established ( n  = 6) treatment group) weeks after initial surgery, animals received MSC injections (0.2ml) to the operated IVD. Three (3-month acute treatment group) and six (6-month acute and established treatment groups) months after initial surgery the L4 multifidus muscle was harvested for muscle fiber type analysis using immunohistochemistry and evaluation of cross sectional area (CSA) of muscle, adipose and connective tissue using standard histology. L2 muscle was harvested for quantitative PCR measures of pro-inflammatory cytokine gene expression (TNF, ΙΛ−1β). Results: Unlike the response to IVD lesion without MSC treatment (increased connective tissue and adipose CSA), acute MSC treatment prevented increase in adipose (acute treatment=control at 3- and 6-months; p  = 0.28 and p  = 0.07) and connective tissue CSA (acute treatment < control at 3-months; p  < 0.001, acute=control at 6-months; p  = 0.39). This paralleled reduced expression of IL-1β at 3-months (acute treatment versus control; p  < 0.001). MCS treatment of established treatment animals restored adipose and connective tissue CSA (established treatment=control at 6 months; P > 0.60). The effect of MSC on muscle CSA depended on the treatment timing. At 6 months, acute treatment animals had larger whole muscle CSA than controls ( p  = 0.002). Control and established treatment animals did not differ ( p  = 0.73). Despite optimistic data for tissue CSA, muscle harvested at 6 months showed reduced proportion of slow muscle fibers and increased intermediate fibers throughout the multifidus muscle (acute and established treatment group versus control; p  < 0.05). TNF expression was greater at 6 months in acute and established treatment groups than control ( p  < 0.001). Conclusion: These results indicate that MSC treatment of the IVD lesion prevents and restores muscle structural changes, but is unable to prevent changes to multifidus muscle fiber type. This is likely to have functional relevance for neuromuscular control of the healed IVD. MSC appear to have and anti-inflammatory effect on muscle in the early phase when IVD is healing, but cannot influence the later elevation of TNF, which appears destructive for muscle fibers.